Дидактический материал к учебнику Э. Р. Нурк, А. Э. Тельгмаа "Математика, 6-й кл.", 1989 (1992)
Экземпляры: КР (20020330) / Инвентарный номер: у42422 / Сис.шифр: 74.26 / Авт.знак: Д 44 / ГРНТИ: 14 / ББК: 74.262.21